Treatment with MOG-DNA vaccines induces CD4(+)CD25(+)FoxP3(+) regulatory T cells and up-regulates genes with neuroprotective functions in experimental autoimmune encephalomyelitis - Fissolo, Nicolás (BioMed Central, 2012)
BACKGROUND: DNA vaccines represent promising therapeutic strategies in autoimmune disorders such as multiple sclerosis (MS). However, the precise mechanisms by which DNA vaccines induce immune regulation remain largely unknown. Here, we aimed to expand previous knowledge existing on the mechanisms of action of DNA vaccines in the animal model of MS, experimental autoimmune encephalomyelitis (EAE), by treating EAE mice with a DNA vaccine encoding the myelin oligodendrocyte glycoprotein (MOG), and exploring the therapeutic effects on the disease-induced inflammatory and neurodegenerative changes. METHODS: EAE was induced in C57BL6/J mice by immunization with MOG(35-55) peptide. Mice were intramuscularly treated with a MOG-DNA vaccine or vehicle in prophylactic and therapeutic approaches. Histological studies were performed in central nervous system (CNS) tissue. Cytokine production and regulatory T cell (Treg) quantification were achieved by flow cytometry. Gene expression patterns were determined using microarrays, and the main findings were validated by real-time PCR. RESULTS: MOG-DNA treatment reduced the clinical and histopathological signs of EAE when administered in both prophylactic and therapeutic settings. Suppression of clinical EAE was associated with dampening of antigen (Ag)-specific proinflammatory Th1 and Th17 immune responses and, interestingly, expansion of Treg in the periphery and upregulation in the CNS of genes encoding neurotrophic factors and proteins involved in remyelination. CONCLUSIONS: These results suggest for the first time that the beneficial effects of DNA vaccines in EAE are not limited to anti-inflammatory mechanisms, and DNA vaccines may also exert positive effects through hitherto unknown neuroprotective mechanisms.